Implementation of Effective Learning convolution Neural Networks For Graphs - Karthikeyan V, Ganesh; Sundaramoorthy, Raj Anand (Journal of Neonatal Surgery, 2025)
For processing graph information, there exists a class of network designs known as Graph Convolutional Networks (GCNs). The complex semantics of the data are typically lost in the existing GCNs' assumption of homogenous graphs, which leads to subpar results. Heterogeneous networks, which intuitively and explicitly express the rich semantical information between nodes, are a more natural way to model several datasets. Minimal effort has been put into developing a GCN for this kind of graph.GRAPH BASED NEURAL NETWORK, or an Attention-Based Heterogeneous Graph Convolutional Network, is what we suggest.GRAPH BASED NEURAL NETWORK is able to obtain more types of links between nodes than any comparable effort has been able to do before because to its effective meta-path generating method. Not only that, but it prioritises values by applying a two-stage convolution based on attention to form node embeddings. An optional pooling layer is included inGraph based neural network to downsample the features while maintaining structural information, making it suitable for graph-level learning problems. Using DBLP and ACM, two transductive graph datasets, and two inductive datasets, we undertake a thorough experimental research (PPI and MUTAG). Classification at the node or graph level shows thatGraph based neural network is far more effective than previous methods.